2018
DOI: 10.1016/j.foodchem.2018.06.138
|View full text |Cite
|
Sign up to set email alerts
|

Covalent binding of food-derived blue pigment phycocyanobilin to bovine β-lactoglobulin under physiological conditions

Abstract: In this study, we investigated structural aspects of covalent binding of food derived blue pigment phycocyanobilin (PCB) to bovine β-lactoglobulin (BLG), major whey protein, by spectroscopic, electrophoretic, mass spectrometry and computational methods. At physiological pH (7.2), we found that covalent pigment binding via free cysteine residue is slow (k = 0.065 min), of moderate affinity (K = 4 × 10 M), and stereo-selective. Binding also occurs at a broad pH range and under simulated gastrointestinal conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Given the versatile and wide use of BSA as a biological carrier of a diverse range of pharmaceutical and nutraceutical compounds, these results point to a possible BSA-PCB stable formulation [ 36 ]. Additionally, PCB also binds to human serum albumin (HSA) [ 37 ] and to bovine β-lactoglobulin (BLG), the main protein composing the milk's whey of cows; this binding was stable in extreme situations, such as an ample pH range and in experimentally modeled gastrointestinal environment [ 38 ]. Interestingly, it was observed that PCB binds to HSA with an affinity similar to BR [ 39 ].…”
Section: Pharmacological Activities Of Pcbmentioning
confidence: 99%
“…Given the versatile and wide use of BSA as a biological carrier of a diverse range of pharmaceutical and nutraceutical compounds, these results point to a possible BSA-PCB stable formulation [ 36 ]. Additionally, PCB also binds to human serum albumin (HSA) [ 37 ] and to bovine β-lactoglobulin (BLG), the main protein composing the milk's whey of cows; this binding was stable in extreme situations, such as an ample pH range and in experimentally modeled gastrointestinal environment [ 38 ]. Interestingly, it was observed that PCB binds to HSA with an affinity similar to BR [ 39 ].…”
Section: Pharmacological Activities Of Pcbmentioning
confidence: 99%
“…The phycocyanobilin (PCB) chromophore is a linear tetrapyrrole present in the phycobiliproteins C‐phycocyanin and allophycocyanin from the Spirulina platensis cyanobacteria. The chemical structure of PCB is similar to biliverdin, and both could be substrates of biliverdin reductase, an enzyme that transforms these compounds into phycocyanorubin or bilirubin, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…This strongly suggests that BLG-BV adducts are not stable in the conditions used in MS/MS. To our knowledge, this is the first time that BLG-BV adducts are detected on a protein by this technique, whereas in a previous study, we were able to detect only one fragment of PCB chromophore bound to BLG but not the whole molecule 11 .…”
Section: Resultsmentioning
confidence: 50%
“…A similar result was obtained for phycocyanobilin (PCB), a BV analogue, in a previous study on BLG. 11 After HP treatment, the covalent BLG-BV adduct is mostly preserved at the monomeric state (Fig. 2A), whereas BLG without ligand is observed at higher MW (not shown).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation